Quantification of total phenol and flavonoid content, in vitro investigation of antioxidant activity and cytotoxic effect of the seed extract of piper nigrum linn (white pepper) - Manzoor, Farzana (BRAC University, 2017)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016